The Role of Plasma Creatine Phosphokinase (CPK) Level in Prediction of Response to Methotrexate for Ectopic Pregnancy - Fatemeh Davari-Tanha; Mohadese Ghazi; Mona Mohseni; Farahnaz Ahmadi (Journal of Family and Reproductive Health, 2016)
Objective: To evaluate the plasma creatine phosphokinase (CPK) level after injection of methotrexate (MTX) as a predictor of treatment success in ectopic pregnancy (EP). Materials and methods: One hundred women treated with single dose of methotrexate for ectopic pregnancy were evaluated in a prospective study, for CPK and ß-subunit of human chorionic gonadotropin (ß-hCG) levels. They received intramuscular MTX at a dose of 50 mg/m2. The day of injection was considered as day 1 (D1). CPK level on the day of Methotrexate injection was compared between success group who were treated by a single MTX injection, and the unsuccessful groupwho were treated by two or three MTX injections or by surgery. Results: The success rate of single dose of MTX injection was 78 (78%). The mean of CPK was higher in success group than unsuccessful group. (86 ± 10.7 vs. 73 ± 11.8), the difference was significant (p = 0.04). The mean of ß-hCG was significantly lower in treatment success group than unsuccessful group (1421.3 ± 443.6 vs. 1925.6 ± 185.4, p = 0.01). Conclusion: The success of single dose of MTX treatment in ectopic pregnancy may be predicted by CPK levels and the higher levels of CPK may be useful for detecting of patients with successful response to MTX.